Educational Tourism In Uzbekistan: A Strategic Direction For Shaping International Image (The Peerian Journal, 2025)
This article analyzes the current state, international trends, and prospects of developing educational tourism in Uzbekistan. Particular attention is paid to enhancing the country's reputation in the international educational arena, attracting foreign students, and shaping an international image by studying the achievements of leading countries in education, especially the Finnish education system, and adapting them to the national system. Additionally, the economic, cultural, and geopolitical significance of educational tourism is examined. The article proposes strategic directions and promising suggestions that should be implemented in the field of educational tourism in Uzbekistan.